Intestinal Parasites in Ducks from Central Jiangsu, China : Epidemiological Survey - Feng, Yu; Wang, Feiyan; Xu, Jinjun; Tao, Jianping; Liu, Dandan (Acta Scientiae Veterinariae, 2026)
Background: Domestic ducks (Anas platyrhynchos domesticus) are essential to rural livelihoods, supplying meat and eggs. However, they are frequently affected by intestinal parasites, primarily helminths and protozoa, which reduce growth, egg yield, and survival. Coccidiosis severely impacts ducklings, with infection rates of 30-60%. As duck farming intensifies, parasite dynamics are shifting. While morphological identification is conventional, it lacks resolution for cryptic species. Molecular tools, particularly ribosomal markers, improve detection and phylogenetic accuracy. This study combines both approaches to assess parasite prevalence and diversity in central Jiangsu. Materials, Methods & Results: Between June and November 2023, fecal samples were collected from 36 duck farms employing diverse rearing systems across 6 districts in 3 cities. Samples were analyzed using morphological methods and PCR amplification of 18S rDNA, ITS, and SSU rRNA gene regions, followed by sequencing. Morphological identification revealed several parasites, including Eimeria anatis, Isospora mandarin, Drepanidotaenia lanceolata, Capillaria spp., and trematode eggs. Molecular data confirmed these findings and further identified associations with reference strains such as Capillaria anatis, Echinostoma miyagawai, and Cryptosporidium baileyi. The overall prevalence of intestinal parasites was 86.11%, with Cryptosporidium spp. most prevalent (58.33%), followed by coccidia (30.56%) and helminths (16.66%). Infection rates varied by region, duck age, and rearing system. Ducks aged 21-50 days exhibited the highest prevalence of Cryptosporidium spp. (71.43%), while older ducks showed higher Eimeria spp. infections. Intensive floor-rearing and water-based free-range systems had higher infection rates than courtyard pasture systems. Discussion: This study revealed a high prevalence and diversity of intestinal parasites in domestic ducks. A 100% infection rate with Cryptosporidium spp. was observed in ducks reared in multilayer cages, despite the absence of helminths or coccidia-likely reflecting hygienic and automated management, though the limited sample size warrants cautious interpretation. Helminth eggs, including D. lanceolata, Capillaria spp., and trematodes, were recovered via nylon-sieve washing and saturated salt flotation. D. lanceolata eggs were distinguished from Fimbriaria fasciolaris by the absence of polar filaments. PCR targeting ITS and 18S rDNA identified trematodes clustering with E. miyagawai and Capillaria spp. with isolates from Gallus gallus domesticus. Coccidian oocysts were preliminarily identified as E. anatis and I. mandarin. The former were ovoid with thick walls and micropyles; high temperature hindered sporulation, complicating differentiation from Tyzzeria perniciosa or Wenyonella philiplevinei. Phylogenetic analysis confirmed E. anatis, while I. mandarin oocysts, containing 2 sporocysts with 4 sporozoites and refractile bodies, showed high similarity (PV785220.1) to waterfowl Eimeria. Close phylogenetic clustering reflects shared Eimeriidae traits in sporozoite development and host invasion. Ecological and immunological characteristics of waterfowl may promote co-infection and niche overlap. Nested PCR targeting SSU rRNA confirmed C. baileyi infection, showing 100% identity with a Passer montanus isolate. While C. baileyi typically infects avian respiratory and intestinal tracts, molecular data on duck-derived isolates in China remain scarce. Overall, this study underscores the substantial burden and diversity of intestinal parasites in ducks from central Jiangsu, emphasizing the importance of integrating morphological and molecular diagnostics. Long-term, large-scale studies are essential for designing targeted control strategies in duck farming systems. Keywords: ducks, intestinal parasites, molecular identification, epidemiology, rearing systems.